Moderasi Beragama dalam Harmoni Sosial : Studi Kasus di Desa Bedono, Kab. Semarang - Meidina Putri; Hava Haniva Ariantara; Imanu Massu Barlinti; Malika Latifah Salma; Salsabila Ilmi Rizqika; Baroroh Sofiati; Putri Rahmawati; Alisa Dewi Rahmawati; Tiara Nabilazen; Haris Mayudaee; Meika Puji Andini; Ghilman Kharizi; Yazid Munawwir; Safrida Khoirun Nisa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the implementation of religious moderation in Bedono Village, Semarang Regency, as a response to religious diversity that has the potential to cause social conflicts. This study aims to analyze the practice of religious moderation, identify supporting and inhibiting factors, and examine its impact on the social life of the community. The research method used is a qualitative approach with case studies, involving observation, in-depth interviews with religious leaders, communities, and documentation studies. The results of the study show that religious moderation in Bedono Village is realized through tolerance, interfaith mutual cooperation, inclusive education, and the celebration of common traditions that strengthen social cohesion. Key supporting factors include inclusive local traditions, education moderation in schools, the active role of youth organizations, community awareness, and village government support. On the other hand, inhibiting factors include a decrease in common traditions, lack of moderation materials in schools, inactivity of youth organizations, low public awareness, and lack of government policies. The positive impact of religious moderation can be seen in increasing tolerance, conflict prevention, strengthening bridges between communities, protecting minority rights, and creating harmony and social peace in society.